Portuguese version of Brown, Trevi\~no and Harrison's Ethical Leadership Scale: Study of its psychometric properties - Vítor Hugo Silva; Ana Patrícia Duarte (Cogent Business & Management, 2022)
This paper investigates the psychometric properties of a Portuguese version of the Ethical Leadership Scale across five field studies. The Portuguese ELS (P-ELS) was compared with subscales of a reduced version of the Ethical Leadership at Work questionnaire to check convergent validity (CFI~=~.95; TLI~=~.95; RMSEA~=~.06) and with subscales of organizational justice scale to confirm discriminant validity (all r <~.18; p <~.05). To assess criterion validity, the extent of the P-ELS's ability to predict organizational ethical climate was tested (all Ø coefficients p <~.01, except for profit subscale). To check nomological validity, the relationship between ethical leadership and job-related affective well-being mediated by leader-member exchange quality was analyzed (B indirect effect~=~0.21; 95% CI~=~0.02, 0.41). Results support P-ELS's unidimensional structure and suggest that it has good construct validity and reliability, therefore, being a useful tool to assess leaders' ethical behaviors in the workplace.
Keywords: 650; construct validity; Ethical Leadership Scale; Portuguese version; reliability; scale validation